Case Report: Novel biallelic moderately damaging variants in RTTN in a patient with cerebellar dysplasia - Romano, Ferruccio; Amadori, Elisabetta; Madia, Francesca; Severino, Mariasavina; Capra, Valeria; Rizzo, Renata; Barone, Rita; Corradi, Beatrice; Maragliano, Luca; Shams Nosrati, Mohammad Sadegh; Falace, Antonio; Striano, Pasquale; et al. (Frontiers in Pediatrics, 2023)
Rotatin, encoded by the RTTN gene, is a centrosomal protein with multiple, emerging functions, including left-right specification, ciliogenesis, and neuronal migration. Recessive variants in RTTN are associated with a neurodevelopmental disorder with microcephaly and malformations of cortical development known as “Microcephaly, short stature, and polymicrogyria with seizures” (MSSP, MIM #614833). Affected individuals show a wide spectrum of clinical manifestations like intellectual disability, poor/absent speech, short stature, microcephaly, and congenital malformations. Here, we report a subject showing a distinctive neuroradiological phenotype and harboring novel biallelic variants in RTTN: the c.5500A>G, p.(Asn1834Asp), (dbSNP: rs200169343, ClinVar ID:1438510) and c.19A>G, p.(Ile7Val), (dbSNP: rs201165599, ClinVar ID:1905275) variants. In particular brain magnetic resonance imaging (MRI) showed a peculiar pattern, with cerebellar hypo-dysplasia, and multiple arachnoid cysts in the lateral cerebello-medullary cisterns, in addition to left Meckel cave. Thus, we compare his phenotypic features with current literature, speculating a possible role of newly identified RTTN variants in his clinical picture, and supporting a relevant variability in this emerging condition.